A Comparative Study: Self-Realization in Twentieth-Century Western Thought, Ibn e Arabi’s Idea, and Theatre of The Absurd - Hadaegh, Bahee (k@ta: A Biannual Publication on the Study of Language and Literature, 2012)
Following humans’ struggles to achieve a better under¬standing of the self throughout major historical periods, the idea of the quest for a whole self is once more rekindled in the anxiety-laden atmosphere of the twentieth century. However, unlike the previous approaches, the twentieth century reflection of the notion of the quest for self-realization is paradoxically revealed in a new model of struggle which inclines more toward spiritual search. This inward struggle manifests itself through connecting the ego to the unconscious world, in line with the theories of Freud and Jung. The similarity which exists between Jung’s psychic state and the Sufis’ mystical world defined by Ibn e Arabi, makes it possible to reconsider the seemingly nihilist readings of the quest for self-realization of the twentieth century absurd thoughts in a positive way